Role of in vitro and in vivo tests of hypersensitivity in beryllium workers. Issue 1 (January 1977) - Price, C D; Williams, W J; Pugh, A; Joynson, D H
Abstract : The value of the beryllium macrophage migration inhibition (Be MIF) and Mantoux tests in the diagnosis of chronic beryllium disease and in the detection of hypersensitivity in healthy beryllium workers is demonstrated. In the absence of steroid treatment the Be MIF test is positive in chronic beryllium disease patients. Seven of 50 (14%) helathy beryllium workers were Be MIF positive, while all the control subjects, normal and sarcoidosis patients, were negative. Healthy beryllium workers tend to be more often Mantoux negative than a comparable group of non-exposed workers, and although not conclusive this finding correlates with a positive Be MIF test. Although the detection of hypersensitivity is not diagnostic of disease, the Be MIF test can be used as an additional method for monitoring the health of beryllium workers. The full significance of our results should be assessed by a long-term study.